Five-year outcomes of western mental health training for Traditional Chinese Medicine practitioners. Issue 1 (December 2016) - Lam, Tai; Mak, Ki; Lam, Kwok; Chan, Hoi; Sun, Kai
Abstract Background There are increasing expectations for primary care practitioners to deal with mental health problems. In Hong Kong, 15 % of the general public consult Traditional Chinese Medicine (TCM) practitioners regularly for their primary health care needs. This study investigated the 5-year outcomes of a western mental health training course for TCM practitioners in Hong Kong. Method Structured questionnaire surveys were conducted to compare the TCM practitioners' confidence and engagement in mental health care before and after the Course. The data collected during 2011–2015 were analyzed. Results A total of 151 TCM practitioners returned both pre- and post-Course questionnaires, with a response rate of 95.6 %. After the course, there were significant increases in the proportions of participants being confident of recognizing patients with psychological problems (62.9 % before the course vs 89.4 % after), diagnosing common mental health problems (47.7 % vs 77.5 %), and managing them (31.2 % vs 64.3 %). Overall, 66.9 % of the participants reported some increase in their confidence in recognizing patients with psychological problems, diagnosing or/and managing patients with common mental health problems. Qualitative responses illustrated the major improvements were increased awareness of mental symptoms, better understanding of classification of mental disorders and management approaches. On the other hand, barriers included difficulties in understanding medical terms in English, consultation time constraints, and a lack of formal referral system to psychiatrists. Conclusions The Course has positive impact on TCM practitioners in handling mental health patients. The findings are useful for designing similar trainings on complementary and alternative medicine practitioners in other countries.